PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN VERBAL - Desi Sommaliagustina; Kantrey Sugiarto (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Verbal violence is often underestimated, even though its impact is very serious on psychological conditions, especially in women and children. The purpose of this study is to identify forms of verbal violence in social practice, analyze legal arrangements regarding verbal violence in the Criminal Code and other laws, and provide recommendations for ideal legal protection for victims. This study examines forms of verbal violence such as catcalling, verbal sexual harassment, and bullying and examines the legal protections available in the Indonesian legal system. Using a normative juridical approach supported by literature studies, this paper analyzes the scope of verbal violence in the Criminal Code (KUHP) and related laws such as the Pornography Law and the Child Protection Law. The results of the study show that despite several applicable legal provisions, understanding and enforcement of the law against verbal violence is still minimal, both in public spaces and in digital media. Therefore, it is necessary to strengthen the legal framework and public education in order to provide comprehensive legal protection for victims.